A Microbial Biosensor Platform for Inline Quantification of Acetate in Anaerobic Digestion: Potential and Challenges. Issue 4 (19th February 2016) - Kretzschmar, Jörg; Rosa, Luis F. M.; Zosel, Jens; Mertig, Michael; Liebetrau, Jan; Harnisch, Falk
Abstract: Real‐time measurement of volatile fatty acids (VFA) in anaerobic digestion (AD) is crucial for process monitoring and management. It is essential for establishing demand‐driven biogas production, however, to date it is not commercially available. A novel microbial electrochemical sensor for inline measurement of acetate and other VFA in AD is proposed. The measurement range as well as the measurement resolution and dynamic behavior of the biosensor were investigated under flow conditions. For application in AD the achieved measurement range is still too low, therefore, measures to improve it as well as further application properties of the sensor are discussed. Abstract : A microbial electrochemical sensor for quantification of volatile fatty acids within anaerobic digestion and other biotechnological applications is proposed. It provides inline data for process control and management, especially allowing automation. Particularly in the case of anaerobic digestion for biogas and electric energy generation, this sensor offers an excellent application potential.